High bacterial load in negative pressure wound therapy (NPWT) foams used in the treatment of chronic wounds. Issue 5 (8th August 2013) - Yusuf, Erlangga; Jordan, Xavier; Clauss, Martin; Borens, Olivier; Mäder, Mark; Trampuz, Andrej
Abstract No earlier study has investigated the microbiology of negative pressure wound therapy (NPWT) foam using a standardized manner. The purpose of this study is to investigate the bacterial load and microbiological dynamics in NPWT foam removed from chronic wounds (>3 months). To determine the bacterial load, a standardized size of the removed NPWT foam was sonicated. The resulting sonication fluid was cultured, and the colony‐forming units (CFU) of each species were enumerated. Sixty‐eight foams from 17 patients (mean age 63 years, 71% males) were investigated. In 65 (97%) foams, ≥ 1 and in 37 (54%) ≥2 bacterial types were found. The bacterial load remained high during NPWT treatment, ranging from 104 to 106 CFU/ml. In three patients (27%), additional type of bacteria was found in subsequent foam cultures. The mean bacterial count ± standard deviation was higher in polyvinyl alcohol foam (6.1 ± 0.5 CFU/ml) than in polyurethane (5.5 ± 0.8 CFU/ml) (p = 0.02). The mean of log of sum of CFU/ml in foam from 125 mmHg (5.5 ± 0.8) was lower than in foam from 100 mmHg pressure (5.9 ± 0.5) (p = 0.01). Concluding, bacterial load remains high in NPWT foam, and routine changing does not reduce the load.